Enhanced two-phase contention window MAC protocol for wireless sensor networks applications - Borges, Luís Miguel Moreira (2014)
This work was supported by the PhD FCT grant SFRH/BD/38356/2007 and IT grant PEst-OE/EEI/ LA0008/2011. I also acknowledge several projects where I was involved in: COST IC1004, COST 2100, MobileMAN, OPPORTUNISTIC-CR, PROENERGY-WSN, Smart-Clothing, and INSYSM